Efficacy of umbilical cord mesenchymal stromal cells for COVID-19: A systematic review and meta-analysis - Yang, Cong-wen; Chen, Ru-dong; Zhu, Qing-run; Han, Shi-jie; Kuang, Ming-jie (Frontiers in Immunology, 2022)
Objectives: A major challenge for COVID-19 therapy is dysregulated immune response associated with the disease. Umbilical cord mesenchymal stromal cells (UC-MSCs) may be a promising candidate for COVID-19 treatment owing to their immunomodulatory and anti-inflammatory functions. Therefore, this study aimed to evaluate the effectiveness of UC-MSCs in patients with COVID-19. Method: Medline, Embase, PubMed, Cochrane Library, and Web of Science databases were searched to collect clinical trials concerning UC-MSCs for the treatment of COVID-19. After literature screening, quality assessment, and data extraction, a systematic review and meta-analysis of the included study were performed. Results: This systematic review and meta-analysis were prospectively registered on PROSPERO, and the registration number is CRD42022304061. After screening, 10 studies involving 293 patients with COVID-19 were eventually included. Our meta-analysis results showed that UC-MSCs can reduce mortality (relative risk [RR] =0.60, 95% confidence interval [CI]: [0.38, 0.95], P=0.03) in COVID-19 patients. No significant correlation was observed between adverse events and UC-MSC treatment (RR=0.85, 95% CI: [0.65, 1.10], P=0.22; RR=1.00, 95%CI: [0.64, 1.58], P=1.00). In addition, treatment with UC-MSCs was found to suppress inflammation and improve pulmonary symptoms. Conclusions: UC-MSCs hold promise as a safe and effective treatment for COVID-19.